Perculiarities of solving communication tasks in teaching foreign language for specific purposes - Tatiana A. Fedorova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This paper deals with language and methodological peculiarities of Foreign Language for Specific Purposes, characteristics of teacher-students communication. The paper is focused on the methods of training Foreign Language for Specific Purposes that provide communication and professional orientation of teaching and involves the practical aspect.